Sistema de trámite documentario y la gestión documentaria en la Municipalidad Provincial de Ucayali – Contamana 2023 - Saldaña Icomena, Lucita Mili (2023)
This study was carried out with the intention of establishing the link between the document processing and processing system and the document administration, in the Ucayali - Contamana 2023 Provincial Municipality, as a non-experimental study application through a sample of 91 workers through a questionnaire which was administered to obtain the necessary results; noting that the processing system was assessed as adequate with a percentage of 81%. In relation to document management, it was evaluated as regular (82%). It was found that there was a significant connection with a positive coefficient of 0.552 between the document processing system and document management. This was compared by the data obtained from the characteristic dimensions, such as the operational process demonstrating a coefficient of 0.517 (p=0.000), information technology with 0.367 (p=0.000) and for the dimension of the system with 0.358 (p=0.000).